Thomas Morus: Utopia (1516) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Arnold Stadler: Mein Hund, meine Sau, mein Leben (1994) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Graham Greene: Die Kraft und die Herrlichkeit (1940) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Gilbert Chesterton: Father Brown (1927) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Ignazio Silone: Brot und Wein (1936) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Heinrich Böll: Ansichten eines Clowns (1963) - Garske, Volker (Christliche Literatur? Ein Kanon für unsere Zeit)

Ergebnisse, Konzepte und Perspektiven für die Berufsausbildungs- vorbereitung. Berichte und Materialien Band 17 - Lippegaus, Petra

Berufsvorbereitende Bildungsmaßnahmen: Kompetenzen feststellen, Ausbildungsreife fördern - Lippegaus, Petra

Well-being and the child-parent relationship at the transition from university to work life - Buhl, Heike M. (Journal of Adolescent Research)
This longitudinal study addresses the impact of the transition from university to work life on emerging adults' well-being and their relationship with their parents. A sample of 102 German students attending their last year at the university (M = 25.44 years, SD = 2.61) completed a questionnaire. Among others, scales from the Network of Relationships Inventory and symptom checklists were administered. Four years later, 51 employed participants of the initial sample were contacted again. During the transition from university to work life, well-being and the relationship with their parents improved. Following a typological approach, two groups of emerging adults were revealed by means of cluster analyses. Well-being in one group increased, whereas well-being in the second group decreased. Group membership was predicted by sex, personality, and the child–parent relationship in university times.

Martin Schongauer, Maler und Kupferstecher : Kunst und Wissenschaft unter dem Primat des Sehens - Heinrichs, Ulrike

Run-time reconfiguration of FPGA-based drive controllers - Schulz, B.; Paiz, C.; Hagemeyer, J.; Mathapati, S.; Porrmann, M.; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Implementation of dynamically reconfigurable control structures on a single FPGA platform - Mathapati, Shashidhar; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Cerium-catalyzed oxidative C–C bond forming reactions - Christoffers, Jens; Werner, Thomas; Rössle, Michael (Catalysis Today)
Keywords: General Chemistry; Catalysis

Hexagon versus Trimer Formation in In Nanowires on Si(111): Energetics and Quantum Conductance - Stekolnikov, A. A.; Seino, K.; Bechstedt, F.; Wippermann, S.; Schmidt, Wolf Gero; Calzolari, A.; Nardelli, M. Buongiorno (Physical Review Letters)

Long-Range Chiral Recognition due to Substrate Locking and Substrate-Adsorbate Charge Transfer - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review Letters)

Quantum conductance of In nanowires on Si(111) from first principles calculations - Wippermann, S.; Schmidt, Wolf Gero; Calzolari, A.; Nardelli, M. Buongiorno; Stekolnikov, A.A.; Seino, K.; Bechstedt, F. (Surface Science)

Atomic scale design of nanostructures - Bernholc, J.; Lu, W.; Nakhmanson, S. M.; Hahn, P.H.; Meunier, V.; Buongiorno Nardelli, M.; Schmidt, Wolf Gero (Molecular Physics)

Steric effects and chirality in the adsorption of glycine and phenylglycine on Cu(110) - Blankenburg, S; Schmidt, Wolf Gero (Nanotechnology)

Ethanol adsorbed on ice: A first-principles study - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Der Vielfalt begegnen – Die Arbeit an der Lerntheke als eine Möglichkeit der inneren Differenzierung im Mathematikunterricht - Aschhoff-Hartmann, Stefanie (Zeitschrift für Heilpädagogik)